Analisis Instrumen Tes Pengambilan Keputusan Taksonomi Presseisen dan Abilitas Peserta Didik Menggunakan Model Rasch: (Analysis of the Presseisen Taxonomy Decision-Making Test Instrument and Learners' Abilities Using the Rasch Model) - Triyanti, Asih; Yuniarti, Anisyah; Afandi, Afandi (BIODIK, 2025)
This study aims to determine the quality of the Presseisen taxonomy decision-making test instrument and students' abilities using Rasch analysis. This research method is descriptive with a quantitative approach. The results showed item validity (item fit) and 12 valid questions. The question's difficulty level (item measure) shows that three questions are very difficult, three are complex, four are easy, and two are straightforward. Reliability shows that the Cronbach alpha value is excellent (0.89), the person reliability value is good (0.85), the item reliability value is excellent (0.98)—the person separation value is 2.41, and the item separation value is 6.85. The individual ability level shows a high category of 124 people, a medium of 49 people, and a low of 190 people. The level of individual suitability shows the fit criteria totalling 237 people, misfit 12 people, and outliers 114 people. Based on the analysis results, it can be concluded that the questions are valid and suitable for use. Penelitian ini bertujuan untuk mengetahui kualitas instrumen tes pengambilan keputusan taksonomi Presseisen dan abilitas peserta didik menggunakan analisis rasch. Metode penelitian ini deskriptif dengan pedekatan kuatitatif. Hasil penelitian menunjukkan Validitas item (item fit) menunjukkan 12 soal valid. Tingkat kesulitan soal (item measure) menunjukkan 3 soal sangat sulit, 3 soal sulit, 4 soal mudah, dan 2 soal sangat mudah. Reliabilitas menunjukkan nilai alpha cronbach bagus sekali (0.89), nilai person reliability bagus (0.85), dan nilai item reliability istimewa (0.98). nilai person separation 2.41 dan nilai item separation 6.85. Tingkat abilitas individu menunjukkan kategori tinggi berjumlah 124 orang, sedang 49 orang, dan rendah 190 orang. Tingkat kesesuaian individu menunjukkan kriteria fit berjumlah 237 orang, misfit 12 orang, dan outlier 114 orang. Berdasarkan hasil analisis, dapat disimpulkan bahwa soal dinyatakan valid dan layak untuk digunakan.